Հայկական ժողովրդական խաղերի ընդհանուր տիպաբանական բնութագիրը տարվա սեզոնային փուլերի համատեքստում - Հռիփսիմե Ասատրյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Народные игры, произрастая из древнейших обрядов, проводились всегда и везде, занимая свое устойчивое место в комплексе армянского цикла праздников. Игры являются магическими действиями или происшествиями, повторяющимися во время конкретного праздника. The folk games that stemmed from ancient ceremonies were held always and everywhere, playing an important role in the whole complex of Armenian holiday cycle. These games are magical actions or events repeating during the certain holiday.
Keywords: Christianity; History of the Armenian Church